2001
DOI: 10.1046/j.1442-9071.2001.00450.x
|View full text |Cite
|
Sign up to set email alerts
|

Ocular adnexal lymphoproliferative disease: a series of 73 cases

Abstract: Background: This study involved 73 patients with lymphoproliferative lesions of the ocular adnexa. The lesions were categorized using the Revised European American Lymphoma classification of lymphoid tissues and analysed to determine the frequency and prognostic impact of tumour type, location, stage and patient's age and sex. Methods: The clinical, histopathological, immunohistochemical and phenotypic analysis by flow cytometry and follow‐up data were studied. Results: The ocular adnexal lymphoproliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
66
3
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(85 citation statements)
references
References 0 publications
12
66
3
4
Order By: Relevance
“…[3][4][5][6]22,23 A higher prevalence in males was only reported in studies originating from Asian countries like Japan 15,24,25 and Korea. 7,[26][27][28] The gender difference seen in our series was due to a higher prevalence of conjunctival disease in females, with no difference at other locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[3][4][5][6]22,23 A higher prevalence in males was only reported in studies originating from Asian countries like Japan 15,24,25 and Korea. 7,[26][27][28] The gender difference seen in our series was due to a higher prevalence of conjunctival disease in females, with no difference at other locations.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 While different subtypes of NHL may present as POAL, extranodal marginal zone lymphoma of mucosa-associated lymphoid tissue (MALT) is the most common histological subtype, accounting for 38% to 64% of POAL cases. [4][5][6][7] Multiple retrospective studies have described clinical and epidemiological features of primary ocular adnexal MALT lymphoma (POAML), including female preponderance, frequent occurrence in the orbit, and increased incidence of bilateral involvement. 8 Association with Chlamydia psittaci infection in certain geographic areas has also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Lymphomagenesis is driven by multiple accumulated genetic abnormalities that determine the survival of neoplastic cells and involve mainly cell-cycle and apoptotic pathways. 7 MALT lymphomas in particular are a paradigm of alternative genetic events, involving different chromosomal aberration and/or apoptosis control protein expression, leading to the deregulation of apoptotic pathways through the activation of the NF-kB pathway.…”
mentioning
confidence: 99%
“…The overall risk of lymphoma related death secondary to DLBCL has been reported as 38%, however a recent study by Madge et al 15 of ocular adnexal DLBCL found that in 11 patients with concurrent systemic disease at presentation, 5-year KaplanMeier survival estimates were 36%. 5 Our patient presented with simultaneous orbital and leptomeningeal involvement, perhaps a unique presentation. Having a high clinical suspicion and early diagnosis and intervention is important in orbital lymphoma cases since there have been reports stating prior or concurrent systemic disease as being the most significant predictive factor for lymphoma-related deaths.…”
Section: Discussionmentioning
confidence: 99%
“…The second most common type is either follicular, 12% to 23%, or DLBCL, 7% to 21%, depending on the study. [4][5][6][7][8][9] The frequency of ocular adnexal lymphoma with localization to the orbit has been cited as 54%. 5 It has been suggested that it may be more appropriate to analyze ocular 10 found that for secondary ocular adnexal lymphoma, follicular type is most common (33%-66%) followed by (in approximate decreasing frequency) multiple myeloma/plasmacytoma, lymphoplasmocytic lymphoma/immunocytoma, mantle cell lymphoma, DLBCL, Burkitt lymphoma, MALT lymphoma and chronic lymphocytic leukemia.…”
Section: Discussionmentioning
confidence: 99%